Integridade pública e capacitação de pessoas: um estudo de caso em empresa pública de Belo Horizonte, Minas Gerais - Simone Piancastelli Jardim (2021)
The objective of this dissertation was to discuss aspects related to the process of implementation of public integrity guidelines in Brazil from the perspective of training, from the study in a public company located in Belo Horizonte, Minas Gerais, during the period 2018 to 2021 Adopted a qualitative approach methodology, a descriptive analysis of the insertion of a municipal public organization in the technical-normative context originating from the anti-corruption movement established in the country was conceived. Documentary data sources categorized into restricted or broad public access were selected in order to investigate the performance of the public company's compliance area by the expression of responsible management, particularly regarding the improvement of the new organizational structure, the conception of ethical culture and the efforts employed in training on the subject of public integrity. Complementarily, there was data collection from a questionnaire and interview with the contribution of the company's management, based on semi-structured questions. The analysis of the results obtained was conceived from sub-themes extracted from the theoretical framework of the dissertation, correlated to technical premises of public governance in integrity, notes on corporate policies and practices of the company under study, and perceptions and feelings reduced to term from questionnaire and interview. Recognizing the limitations of research on the legislative framework under construction, the technical rigor in the design of new procedures in public management and, additionally, in conducting a field research in circumstances of the COVID-19 pandemic, with corresponding and severe restrictions, there were results interpreted as positive for the expansion of ethical culture in local governments. As identified in the literature as a characteristic of Latin American organizations, the municipal public company demonstrates its commitment to the theme of public integrity and must renew actions to disseminate its practices in this regard, in order to become a model for implementing local integrity program and demonstrate its efforts to introduce innovative techniques in terms of training.